1997
DOI: 10.1097/00007632-199705150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Physical Work Activities as Predictors of Future Low Back Pain

Abstract: Occupational activities, particularly in women, such as working with heavy weights or lengthy periods of standing or walking, were associated with the occurrence of low back pain. Short-term influences may be more important in the occurrence of new episodes rather than cumulative lifetime exposure, and emphasize that such morbidity may be avoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(120 citation statements)
references
References 27 publications
8
109
0
3
Order By: Relevance
“…The occupational groups with the highest incidence rates in the UK are construction workers and clerks among males and domestic household workers and professionals among females [42]. Finally, Guo's representative data on the prevalence of back pain for the working population of the USA [24] indicates that the main highrisk occupations are carpenters and car mechanics among males and nurses, and nursing orderlies, and related occupations among females.…”
Section: Occupational Groups and Back Painmentioning
confidence: 99%
See 2 more Smart Citations
“…The occupational groups with the highest incidence rates in the UK are construction workers and clerks among males and domestic household workers and professionals among females [42]. Finally, Guo's representative data on the prevalence of back pain for the working population of the USA [24] indicates that the main highrisk occupations are carpenters and car mechanics among males and nurses, and nursing orderlies, and related occupations among females.…”
Section: Occupational Groups and Back Painmentioning
confidence: 99%
“…Information on specific work-related risk factors is particularly valuable for its preventive potential. For example, unphysiological posture and repetitive carrying, lifting and holding heavy loads are the most conclusively documented work-related risk factors for back pain [7,12,24,42,50,62], although experts disagree as to the specific biomechanical mechanisms of action involved [64]. More in-depth analyses of our data (not presented here) show approximately identical pain scores for 0-7 h of manual labour, and a sharp increase to much higher pain scores for subjects with daily exposure to more than 7 h of heavy manual labour.…”
Section: Socioeconomic Status Risk Factors and Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that subjects spending at least 50% of the working time in a standing position are in risk for developing neuromusculoskeletal impairments and venous insufficiency (Krijnen et al, 1998;Macfarlane et al, 1997;Tomei et al, 1999). The static contraction of lower back and legs results in diminished function of the calf muscle, muscle fatigue, discomfort and even low back pain (Krijnen, et al, 1998).…”
Section: Wearing Unstable Shoes Can Be a Beneficial Ergonomic Intervementioning
confidence: 99%
“…In a study by MacFarlane et al [8], a population-based cohort was followed for 12 months. An increased risk of low back pain in jobs involving work Abstract Factors important for avoiding back disorders in different age-groups have seldom been compared and studied over time.…”
Section: Introductionmentioning
confidence: 99%